Growth, microstructure and thermal transformation behaviour of epitaxial Ni-Ti films. (15th June 2017) - Kauffmann-Weiss, S.; Hahn, S.; Weigelt, C.; Schultz, L.; Wagner, M.F.-X.; Fähler, S.
Abstract: Epitaxial films have the potential to be used as model systems for fundamental investigations on the martensitic transformation in binary NiTi. In this paper, we discuss growth of binary NiTi thin films on single crystalline MgO substrates. Sputter deposition is used to grow NiTi films. Films prepared by complementary preparation routes (with different deposition temperatures and subsequent heat treatments) are investigated by X-ray diffraction, electron microscopy, atomic force microscopy, and electrical resistivity measurements, with the aim of optimizing film properties, particularly to obtain a well defined orientation of the austenitic unit cell and smooth surfaces. Our results show that deposition at elevated temperatures and carefully controlled subsequent heat treatments allow to produce epitaxially grown and smooth NiTi films that exhibit reversible one- or two-step martensitic transformations. Graphical abstract: Image 1